2023
DOI: 10.1021/acs.chemrev.2c00546
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Oxide: Phase Diagrams, Structures, Synthesis, and Applications

Abstract: Vanadium oxides with multioxidation states and various crystalline structures offer unique electrical, optical, optoelectronic and magnetic properties, which could be manipulated for various applications. For the past 30 years, significant efforts have been made to study the fundamental science and explore the potential for vanadium oxide materials in ion batteries, water splitting, smart windows, supercapacitors, sensors, and so on. This review focuses on the most recent progress in synthesis methods and appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(80 citation statements)
references
References 479 publications
(770 reference statements)
0
59
0
Order By: Relevance
“…The crystal structure of VO 2 will be transformed as the temperature changes and this phase change temperature is 68 °C, which leads to many kinds of VO 2 crystal forms in nature. There are mainly tetragonal VO 2 (A), monoclinic VO 2 (M), VO 2 (D), and VO 2 (B), tetragonal rutile VO 2 (R), and triclinic VO 2 (T), [ 9 ] which can have mutual transformation between them under certain conditions. Presently, a variety of vanadium dioxide polymorphs (A‐, B‐, D‐, and M‐VO 2 ) have been demonstrated to act as cathode materials for AZMB and deliverability of Zn 2+ ions storage [7b,10]…”
Section: Crystal Structure and Zn2+ Ion Storage Mechanism Of Vo2mentioning
confidence: 99%
“…The crystal structure of VO 2 will be transformed as the temperature changes and this phase change temperature is 68 °C, which leads to many kinds of VO 2 crystal forms in nature. There are mainly tetragonal VO 2 (A), monoclinic VO 2 (M), VO 2 (D), and VO 2 (B), tetragonal rutile VO 2 (R), and triclinic VO 2 (T), [ 9 ] which can have mutual transformation between them under certain conditions. Presently, a variety of vanadium dioxide polymorphs (A‐, B‐, D‐, and M‐VO 2 ) have been demonstrated to act as cathode materials for AZMB and deliverability of Zn 2+ ions storage [7b,10]…”
Section: Crystal Structure and Zn2+ Ion Storage Mechanism Of Vo2mentioning
confidence: 99%
“…Vanadium is an important strategic metal with a vast range of applications in the metallurgical industry, chemical industry, battery, medicine, and other fields. Currently, vanadium slag is the main direct raw material for vanadium extraction, which is the vanadium-containing tailings in the titanomagnetite steelmaking process. The typical commercial process of vanadium recovery from vanadium slag involves sodium roasting–water leaching, the principle of which is to convert the insoluble spinel (FeV 2 O 4 , V 3+ ) in vanadium slag into soluble sodium metavanadate (NaVO 3 , V 5+ ) via full oxidation roasting; then it can be leached by water. The leaching solution requires further purification and precipitation to prepare vanadium oxide (V 2 O 5 ) as the final product. , …”
Section: Introductionmentioning
confidence: 99%
“…Hybrid organic–inorganic vanadium oxides represent an attractive target owing to the relative abundance and low cost of vanadium, [33] the ease with which its multiple oxidation states can be accessed, [34] and the varied coordination geometries that vanadium centers can adopt [35–37] —implying structural tunability. Indeed, numerous examples of hybrid vanadium oxides have been reported that demonstrate the wide scope of accessible zero‐, one‐, two‐, and three‐dimensional inorganic connectivities as well as a range of organic molecules that can be included in this broad class of materials [32,37–43] .…”
Section: Introductionmentioning
confidence: 99%